The Effect of Organisational Culture on Employee Wellbeing in Early-Stage High Growth Startups - Al-Khafaji, Sami (My University, 2025)
Startups carry a promise of changing the world fast, but that same speed can quietly wear down the people doing the building. This thesis examines how organisational culture in early-stage high-growth startups shapes employee wellbeing, asking: how does startup culture affect employee wellbeing in these environments? The work is conceptual and theory-driven, drawing on institutional theory, Schein’s organisational culture model, the Job Demands–Resources (JD-R) framework and Work–Life Boundary theory to build a multi-level view of the problem. The thesis proceeds in three steps. First, it identifies the key factors that shape organisational culture in high-growth startups, from founder imprinting and hiring practices to investor expectations and wider ecosystem logics. Second, it analyses how this culture translates into both demands (long hours, uncertainty, blurred boundaries, ownership pressure) and resources (autonomy, purpose, learning) that together influence employee wellbeing. Third, it explores practices that could support wellbeing in high-growth settings, such as clearer work–life boundaries, systematic feedback and support structures, and better tracking of wellbeing over time. It also examines why these practices are often not adopted under current growth and funding norms. The thesis shows that startup culture is a double-edged sword. The same mechanisms that enable rapid scaling can also create fragile, unsustainable conditions for employees and founders. By reframing wellbeing as a long-term asset rather than a cost, the thesis argues that startups can evolve towards growth models that keep both performance and people at the centre.

Startupit ovat innovatiivisia yrityksiä, joiden toiminta perustuu usein skaalautuvuuteen ja uuden teknologian luontiin. Startupit tähtäävät nopeaan kasvuun, jolla voi olla merkittäviä hyötyjä pidemmällä aikavälillä yrityksen menestykseen. Nopea kasvu voi kuitenkin myös aiheuttaa haittoja johtajille ja työntekijöille vallitsevan startup-kulttuurin aiheuttamana. Tässä kandidaatintutkielmassa tarkastellaan, miten organisaatiokulttuuri vaikuttaa työntekijöiden hyvinvointiin alkuvaiheen nopeasti kasvavissa startupeissa.Tutkielman pääkysymys on: miten organisaatiokulttuuri vaikuttaa työntekijöiden hyvinvointiin alkuvaiheen nopeakasvuisissa startupeissa? Tutkielma on teoreettinen kirjallisuuskatsaus. Analyysissa hyödynnetään institutionaalista teoriaa ulkoisten paineiden ja startup-ekosysteemin normien jäsentämiseen, Scheinin organisaatiokulttuurimallia kulttuurin muodostumisen selittämiseen sekä työn vaatimusten ja voimavarojen -mallia (JD-R) ja Work-Life Boundary teoriaa hyvinvoinnin tarkasteluun. Näiden avulla hahmotetaan, miten startupien perustajien päätökset, rekrytointi, sijoittajien odotukset ja ekosysteemin kasvupaineet muovaavat kulttuuria, joka tuottaa samanaikaisesti sekä kuormitusta (pitkät työtunnit, epävarmuus, epäselkeät rajat työssä) että voimavaroja (autonomia, merkityksellisyys, oppiminen). Tutkielman tulokset osoittavat, että startup-kulttuuri voi vaikuttaa työntekijöiden hyvinvointiin sekä positiivisesti että negatiivisesti. Tähän tulokseen päädytään analysoimalla, miten mekanismit, jotka mahdollistavat nopeaa kasvua, voivat myös heikentää työntekijöiden ja johtajien hyvinvointia. Johtopäätöksenä esitetään, että hyvinvointi tulisi nähdä osana kestävää kasvua, eikä sen vastakohtana. Kestävimpien toimintatapojen mahdollistamiseksi tulisi huomioida hyvinvointia samalla tasolla kasvutavoitteiden kanssa.
Keywords: Organisational culture, employee wellbeing, high-growth startups, job-demands resources (JD-R), work-life boundaries, institutional theory, Organisaatiokulttuuri, työntekijä hyvinvointi, startupit, työn vaatimusten ja voimavarojen -malli, institutionaalinen teoria, Work-Life Boundary -teoria